A new rapid thermographic method to assess the fatigue limit in GFRP composites. (15th October 2016) - Palumbo, Davide; De Finis, Rosa; Demelio, Pompeo Giuseppe; Galietti, Umberto
Abstract: Conventional procedures and methods used for obtaining the fatigue performance of materials represent a critical aspect of mechanical characterization because of time consuming tests with a high number of specimens. In the last few years, great efforts have been made to develop a number of methods aimed at reducing testing time and, subsequently, the cost of the experimental campaign. In the process, thermographic methods have shown to be a useful tool for the rapid evaluation of fatigue damage and fatigue limit. This work deals with a new procedure for the evaluation of fatigue limit and the monitoring of damage in GFRP material by means of thermography. Although damage mechanisms in composite materials are difficult to understand, the proposed procedure allows us to obtain a number of parameters providing information relating to the onset of failure phenomena. It is worth noting that the reported procedure provides results in good agreement with those attained by the standard test methods.